Assessing the evolution of wheat grain traits during the last 166 years using archived samples - Sinda Ben Mariem (Nature Portfolio, 2020)
Abstract The current study focuses on yield and nutritional quality changes of wheat grain over the last 166 years. It is based on wheat grain quality analyses carried out on samples collected between 1850 and 2016. Samples were obtained from the Broadbalk Continuous Wheat Experiment (UK) and from herbaria from 16 different countries around the world. Our study showed that, together with an increase in carbohydrate content, an impoverishment of mineral composition and protein content occurred. The imbalance in carbohydrate/protein content was specially marked after the 1960’s, coinciding with strong increases in ambient [CO2] and temperature and the introduction of progressively shorter straw varieties. The implications of altered crop physiology are discussed.